Enhancing education supervision in Saudi Arabia – towards eSupervision - Amin Alzahrani; Mohammed Alghamdi (Educational Futures)
This paper explores the ways in which education supervision in the Kingdom of Saudi Arabia might be enhanced by the use of digital technologies to supersede the traditional model which is based on face-to-face meetings between supervisor and teachers. Education supervisors are government employees who have the responsibility of overseeing and developing the capability of teachers in public schools. With a rapidly growing population it is becoming almost impossible for supervisors to provide adequate support for the average 70 teachers for whom they have responsibility, especially given that the teachers are often geographically widespread. Whilst government investment and interest has been made into exploring distance supervision via electronic communication systems (eSupervision) such initiatives have not yet proved successful. The authors of this paper have both developed approaches to eSupervision that are based respectively on use of existing Internet tools and through the development of a bespoke electronic education management system (EEMS). Both research studies are reported here and show that the realisation and application of the potential of such technologies in the educational supervision process will require a concentrated training effort for supervisors and teachers alike.